The Effect of Different Extraction Methods on Total Tannin Content of Methanol Extract of Simpur Air Leaves (Dillenia suffruticosa) - Wahyuni, Sri; Masriani, Masriani; Sasri, Risya; Sapar, Ajuk; Erlina, Erlina; Ersando, Ersando (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The use of metal mordants in fabric dyeing can harm the environment and health, so it is necessary to look for natural mordants that are more environmentally friendly. The utilization of Simpur Air leaves (Dillenia suffruticosa) as a biomordant is one of the efforts to produce a more environmentally friendly tannin mordant. D. suffruticosa has been reported to contain tannin compounds in all parts of the plant. However, scientific evidence of differences in the total tannin content of methanol extracts of D. suffruticosa leaves with various extraction methods have not been found so far. This study aims to determine the effect of different extraction methods on the yield value and total tannin content of methanol extracts of D.suffruticosa leaves using UV-Vis spectrophotometric method at a wavelength of 755.8 nm with Folin Ciocalteau reagent. D. suffruticosa leaves are extracted by using three methods, namely maceration, soxhletation and reflux. Tannic acid is used as a comparator. The results show that the yield value of D. suffruticosa leaves extracted by maceration, soxhletation and reflux methods were 8.35%; 12.26%; and 25.24%, respectively. The total tannin content of methanol extract of D. suffruticosa leaves with maceration method is 0.15% Â± 0.007; soxhletation is 0.18% Â± 0.007 and reflux is 0.21% Â± 0.016.Â Based on the results of the data analysis, the significance value <0.05 was obtained. It can be concluded that the extraction method affects the yield value and total tannin content of methanol extract of D. suffruticosa leaves.